1995
DOI: 10.1247/csf.20.355
|View full text |Cite
|
Sign up to set email alerts
|

Morphofunctional Study of the Haemocytes of the Bivalve MolluscMytilus galloprovincialis with Emphasis on the Endolysosomal Compartment.

Abstract: ABSTRACT. In the present work the haemocytes of mussels Mytilus galloprovincialis (Mollusca, Bivalvia) have been studied by light and electron microscopy in order to describe their main morphological features and to relate these to their roles in immune defence. The haemocytes belong to two definitive differentiated types, hyalinocytes and granulocytes. The former shows the presence of several fine pseudopodial protrusions, large nucleus with clumps of dense chromatin, scant cytoplasm, a well developed Golgi a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
65
1
7

Year Published

1995
1995
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 130 publications
(79 citation statements)
references
References 34 publications
6
65
1
7
Order By: Relevance
“…This is in agreement with microscopic observations, and indirectly with enzyme studies, which have shown that granulocytes have abundant 259 Fig. 5 (continued) lysosomes (Pipe 1990, Cajaraville & Pal 1995, Cima et al 2000, Matozzo et al 2007.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…This is in agreement with microscopic observations, and indirectly with enzyme studies, which have shown that granulocytes have abundant 259 Fig. 5 (continued) lysosomes (Pipe 1990, Cajaraville & Pal 1995, Cima et al 2000, Matozzo et al 2007.…”
Section: Discussionsupporting
confidence: 88%
“…Resale or republication not permitted without written consent of the publisher Pal 1995, López et al 1997, Pipe et al 1997, Cima et al 2000, Chang et al 2005, Zhang et al 2006, Aladaileh et al 2007, García-García et al 2008. Interspecies variability and methodological differences in specimen collection and processing have been considered the principal reasons for the current lack of consensus on the actual number of distinct haemocytic subpopulations that can be discerned morphologically (see reviews in Cheng 1981, 1984, Auffret 1988, Hine 1999.…”
Section: Abstract: Mya Arenaria · Vibrio Splendidus · Haemocyte Subpmentioning
confidence: 99%
“…In the same cell types there are usually other granules which lack acid hydrolases. Two main cell types are distinguished in the haemolymph of several bivalve molluscs: the non-granular hyalinocytic haemocyte and the granule-containing granulocytic haemocyte [2,3,7,10,30]. These haemocytes constitute the main internal defense system in molluscs, which is brought about by humoral factors and mainly by phagocytosis and cell-mediated cytotoxicity [1].…”
mentioning
confidence: 99%
“…unit/hemolymph lL with r 2 = 0.9925 responses in fresh hemolymph samples. This result can be accounted for by interindividual diffrences in total hemocyte count or in distribution between circulating and infiltrated cells, as already suggested (Cajaraville and Pal 1995;Hoher et al 2012;Hughes et al 1991;Li et al 2008), but also by a poor reproducibility in hemolymph sampling. However, in our experients, MTT OD varied linearly as a function of plated hemolymph volumes.…”
Section: Discussionmentioning
confidence: 92%
“…In particular, whereas different types of hemocytes have been described so far (Cajaraville and Pal 1995;Friebel and Renwrantz 1995;Hine 1999;Le Foll et al 2010;Parisi et al 2008;Donaghy and Volety 2011), the origin, the role and the activation steps of hemocyte subpopulations are unknown. Furthermore, except for phagocytosis (GarciaGarcia et al 2008;Le Foll et al 2010;Voccia et al 1994), consensual protocols quantifying hemocyte activity or functional markers of inflammatory states are still lacking.…”
Section: Introductionmentioning
confidence: 99%